An Examination of New York State's Integrated Primary and Mental Health Care Services for Adults with Serious Mental Illness - Scharf, Deborah M. (RAND Corporation, 2014)
Several ongoing New York state initiatives promote integrated care for adults with serious mental illness, provided or coordinated by community mental health center staff. This report examines Primary and Behavioral Health Care Integration grants, Medicaid Incentives, and Medicaid Health Homes and concludes with recommendations for strengthening state integrated care initiatives.